The Case of the Kaliwa Dam Project in Quezon Province, Philippines: Curbing Contentions Through Active Deliberation Among Indigenous and Marginalized Communities - Maningo, Clyde Andaya (Graduate Review of Political Science and Public Administration Journal, 2023)
The consensus on what a city must be was embodied in The City We Need: Principles for a New Urban Paradigm, which the World Urban Campaign partners envisioned to strive for a more sustainable future. The first paradigm argues that “the city we need is socially inclusive and engaging.” However, this was not always the case, especially in constructing the Kaliwa Dam. Despite the objective of providing a long-term solution for NCR’s water shortage, the construction of Kaliwa Dam in Quezon Province, Philippines—through China’s Official Development Assistance (ODA), allotted 18.7 billion pesos administered through the China Energy Engineering Corporation (CEEC) — has been shrouded with controversies. This includes violating legal processes, complete disregard for biodiversity issues, the human consequences and neglect of indigent rights, the technocratic criticisms of the geographic danger it poses, and the incurred debt insinuated in related cases of China’s loan trap. Through document research and secondary data analysis of persisting discourses on the subject, this paper tries to expound these issues and correspond them with the necessity for multi-stakeholder cooperation. It also aims to explore viable solutions to aid the water scarcity problem while limiting the degradation effects incurred to the social dynamics and environment. Further, the analysis abides by the ongoing opposition and struggle of indigenous communities to halt the ongoing Kaliwa Dam construction—clinging to the necessity to push for the theoretical framework of deliberative policy analysis in solving the potent issues of indigenous marginalization in policy formulation processes.